New magnetic bimetallic yanus-like Ag-Fe nanoparticles for antitumine therapy - O. V. Bakina; A. V. Pervikov; E. A. Glazkova; N. V. Svarovskaya; A. S. Lozhkomoev; M. I. Lerner; A. V. Avgustinovich (Сибирский онкологический журнал, 2019)
The purpose of the study was to analyze the antitumor activity of magnetic bimetallic Ag-Fe nanoparticles having the structure of Yanus particles produced by the electrical explosion of wires. material and methods. For the synthesis of bimetallic Ag-Fe nanoparticles, a simultaneous electric explosion of silver and iron wires in an argon atmosphere was used. The morphology and size of the nanoparticles and their agglomerates were determined by transmission electron microscopy. To determine the average size of nanoparticles, particle size distribution histograms approximated by log-normal distribution were plotted. The phase composition was determined using x-ray method. The cytotoxic effect of the nanoparticles was evaluated by MTT assay using mouse neuro-2a (N2a) neuroblastoma cell lines and J774 histiocytic sarcoma cell lines. results. In case of simultaneous electric explosion of silver and iron wires in an argon atmosphere, the spherical 72 nm particles were obtained. Silver and iron were shown to be unevenly distributed in particles. There were areas enriched with one of the components with clear boundaries of phase separation or Janus nanoparticles. On the diffractogram of the sample, the main reflections correspond to the phases of metallic Ag and Fe. Aqueous suspensions of monometallic Ag and Fe nanoparticles reduced cell viability to a lesser extent than bimetallic nanoparticles. Ag-Fe nanoparticles showed the highest dose-dependent antitumor activity. The higher corrosion rate of bimetallic Ag-Fe particles compared to monometallic nanoparticles was due to the larger contact area between metallic phases in Janus nanoparticles, which determined a larger number of corrosion centers in bimetallic nanoparticles. conclusion. As a result of an electric explosion of wires from immiscible metals of iron and silver, bimetallic Ag-Fe nanoparticles with Janus particle structure were obtained. Ag-Fe nanoparticles exhibite higher antitumor activity than the individual metals from which they are composed and are a promising material for the fight against cancer cells.